EDD 734: Dissertation Research IV
An S-factor course with Dissertation Chairs. Students will work closely with their dissertation chair to write Discussion, Introduction, and Abstract sections for their dissertation-in-practice. In addition, students will orally defend their dissertation and shepherd it through the publication process.